Dynamic Response of an FRP Footbridge Due to Pedestrians and Train Buffeting. (2017) - Russell, Justin; Wei, Xiaojun; Živanović, Stana; Kruger, Casper
Abstract: Fibre-Reinforced Polymers (FRPs) are an increasingly popular option for the construction of bridges as they possess high strength to weight properties and good durability qualities. In particular, they are well suited to pedestrian bridges over railway lines as they can be installed without much disruption and require little maintenance. However, as they are typically lighter and less stiff than traditional materials there is concern about their dynamic response in such locations both due to human induced actions and as a train buffeting. During such events, the aerodynamic loading from the movement of the train causes a buffeting effect on the bridge and may result in vibrations which exceed pedestrian comfort limits. There is currently a lack of experimental information on this subject, and further data is needed if such bridges are to be used on future lines, especially with higher speed limits. This paper presents an experimental investigation of the response of a 14.5m FRP truss bridge due to crowd loading and train buffeting. First the hammer impact tests were conducted to identify the vertical and lateral modes of interest, and their frequencies and damping. An array of accelerometers were used to measure the vertical and lateral vibrations during two crowd loading events with 15 and 8 people walking continuously, and multiple train passes. The results were then compared to serviceability guideline limits. These results add to the understanding of the vibration response of FRP bridges and can be used to help designers assess conditions in which such effects become critical.